High-Tech Trash Glitch, Noise, and Aesthetic Failure - Kane, Carolyn L. (University of California Press, 2019)
High-Tech Trash analyzes creative strategies in glitch, noise, and error to chart the development of an aesthetic paradigm rooted in failure. Carolyn L. Kane explores how technologically influenced creative practices, primarily from the second half of the twentieth and first quarter of the twenty-first centuries, critically offset a broader culture of pervasive risk and discontent. In so doing, she questions how we continue onward, striving to do better and acquire more, despite inevitable disappointment. High-Tech Trash speaks to a paradox in contemporary society in which failure is disavowed yet necessary for technological innovation. "Leonard Cohen sang 'There's a crack in everything...that's how the light gets in.' Here, Carolyn Kane teaches us how to see that light, one crack at a time." FRED TURNER, author of The Democratic Surround: Multimedia and American Liberalism from World War II to the Psychedelic Sixties "Kane profiles art practices and media discourses that exploit and celebrate, rather than filter or suppress, all kinds of errors and noises. A welcome intervention in a number of discursive fields." PETER KRAPP, author of Noise Channels: Glitch and Error in Digital Culture "An original work of scholarship that addresses some of the most pervasive phenomena and foundational questions in the contemporary media environment." ROBERT HARIMAN, coauthor of The Public Image: Photography and Civic Spectatorship CAROLYN L. KANE is Associate Professor of Communication at Ryerson University and author of Chromatic Algorithms: Synthetic Color, Computer Art, and Aesthetics after Code.